Uncovering the influence of social media marketing activities on Generation Z’s purchase intentions and eWOM for organic cosmetics - Gia Khuong An; Thi Thuy An Ngo (PLoS ONE, 2025)
The organic cosmetics market in Vietnam is rapidly growing, especially among Generation Z consumers who prioritize sustainability and eco-friendly products. Despite this expansion, the key factors driving purchasing decisions for organic cosmetics have not been adequately researched. This study addresses this gap by examining the influence of Social Media Marketing Activities (SMMAs) on Generation Z’s purchase intentions and eWOM, with perceived quality and perceived value as mediating factors. Using a quantitative approach, data were collected from 315 Generation Z participants in Vietnam through a structured questionnaire. The study explores various dimensions of SMMAs—interaction, customization, trendiness, and entertainment—and their effects on perceived quality, perceived value, eWOM, and purchase intention. Results show that SMMAs have a stronger impact on perceived quality (β = 0.726) than on perceived value (β = 0.503), suggesting that social media marketing strategies are particularly effective in shaping how Generation Z evaluates product quality. Additionally, perceived quality significantly influences perceived value (β = 0.312), eWOM (β = 0.346), and purchase intention (β = 0.279). Similarly, perceived value positively impacts eWOM (β = 0.395) and purchase intention (β = 0.402), while eWOM itself plays a direct role in driving purchase intention (β = 0.167). These findings highlight the interconnected role of social media marketing in influencing consumer behavior through both direct and mediated effects. This research provides strategic direction for brands in Vietnam’s organic cosmetics sector targeting Generation Z. By leveraging these findings, brands develop targeted social media campaigns that emphasize quality perceptions through interactive content and customized experiences, thereby effectively driving both purchase decisions and positive eWOM among Generation Z consumers.